Anti-gout Medications and Risk of Cardiovascular Disease: A Nested Case-Control Study - Chuang, Tsung-Ju; Wang, Yu-Hsun; Wei, James Cheng-Chung; Yeh, Chih-Jung (Frontiers in Medicine, 2021)
INTRODUCTION Gout is the leading cause of inflammatory arthritis and is also associated with multiple comorbidities such as cardiovascular disease (CVD), whose future risk can be lowered by urate-lowering therapy (ULT) in gouty patients. It is, however, still not clear whether its effect is associated with the days of usage and the adherence rate of ULT. Methods: A 2000–2012 retrospective cohort study was conducted, and all investigated subjects were identified by the International Statistical Classification of Diseases and Related Health Problems, 9th Revision, Clinical Modification. Data were collected from Taiwan’s National Health Insurance Research Database (NHIRD) and conditional logistic regression was used to evaluate the odds ratio of CVD in relation to the days of usage and to the adherence rate of ULT (benzbromarone and allopurinol) after the adjustment for potentially confounding variables. Results: A total of 3706 gout patients with and without CVD have been included in the final analysis after a 1:1 propensity score that matched for age, sex, comorbidities, aspirin, and statin. The days of usage of allopurinol was <180 days and benzbromarone, in its turn, presupposed a higher risk of CVD. The adherence rate of allopurinol >= 0.7 has a lower CVD risk (adjusted OR: 0.66 95% CI: 0.46- 0.96) whereas the adherence rate of benzbromarone >= 0.7 has a lower CVD risk (adjusted OR: 0.68 95% CI: 0.50- 0.91). The subgroup analysis revealed the adherence rate >= 0.7 of ULT with a lower CVD was only found to be present in males and at an age <65. Furthermore, the correlations are more pronounced in the ischemic heart disease subgroup than in the cerebrovascular disease group. Conclusion: This study reveals that gout patients taking ULT (allopurinol and benzbromarone) with an adherence rate >= 0.7 are at a decreased risk of developing CVD, especially with younger age (<65) and if they are male. On top of this, the benefit is more pronounced in ischemic heart disease. Despite further prospective trials needing to be warranted to confirm our findings, health care providers may, bearing these conclusions in mind, emphasize the importance of adherence to ULT in gout patients.